Green Investment Strategies for Sustainable Ecotourism Development in Gili Trawangan: A North Lombok Youth Perspective - Sari, Ni Kadek Wahyuni Merta; Azim, Muhammad; Uli, Aprilla Sinta Uli Sinta; Alfarizi, Moh Salman; Yasa, I Putu Buda (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the influence of financial literacy, motivation, environmental concern, and local ESG support on the intention and behavior of green investment among youth in North Lombok, particularly in the context of sustainable ecotourism development. The research employs a quantitative descriptive-verificative approach using Structural Equation Modeling – Partial Least Squares (SEM-PLS). A total of 100 respondents, aged 17–30 years from the subdistricts of Pemenang, Tanjung, and Kayangan, were selected through purposive sampling. The results indicate that all independent variables have a positive and significant effect on green investment intention, while investment intention strongly influences actual green investment behavior (β = 0.739; p < 0.001). Although 60% of respondents hold only a high school education and the overall human resource quality has not yet fully supported green investment practices, 74% expressed a high interest in participating in sustainable investment if accompanied by appropriate training and local government support. The model shows an R² value of 0.638 for investment intention and 0.571 for green investment behavior, with Q² = 0.462, indicating good predictive relevance. These findings emphasize the importance of strengthening green financial literacy, socio-economic motivation, and multi-stakeholder collaboration among government, communities, and educational institutions to enhance youth participation in sustainable investment and ecotourism development.